2014
DOI: 10.1111/obr.12140
|View full text |Cite
|
Sign up to set email alerts
|

Excess adiposity and survival in patients with colorectal cancer: a systematic review

Abstract: Excess adiposity is an established risk factor for incident colorectal cancer (CRC) but whether this association extrapolates to poorer survival is unclear. We undertook a systematic review to examine relationships between measures of adiposity and survival in patients with CRC. For distinction, we included pre-diagnosis exposure and CRC-related mortality. We performed dose-response meta-analyses and assessed study quality using eight domains of bias. Six study categories were identified based on (i) timing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 73 publications
(169 reference statements)
3
78
2
Order By: Relevance
“…Similar results have been shown for other major surgical cancer procedures [11]. However, in a recent review, Parkin et al draw the conclusion that there is little evidence supporting a strong link between adiposity and survival in patients with CRC [12].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Similar results have been shown for other major surgical cancer procedures [11]. However, in a recent review, Parkin et al draw the conclusion that there is little evidence supporting a strong link between adiposity and survival in patients with CRC [12].…”
Section: Introductionmentioning
confidence: 68%
“…It has been used for that purpose since the early 1980s [25], and in a recent study using CT, it was shown that obese stage II CRC patients were at higher risk for poor outcome, with significantly worse disease-free survival than patients with less visceral fat [24]. A possible explanation for such findings may be that excess visceral adiposity seems to induce a pro-tumorigenic environment through metabolic, immunologic, and endocrine processes involving chronic inflammation, insulin resistance, and increased levels of insulin-like growth factor [12,26,27].…”
Section: Discussionmentioning
confidence: 91%
“…Year of diagnosis However, the evidence for the role of most risk factors (such as obesity [23][24][25][26]) and cancer prognosis is mixed and depends on the cancer type.…”
Section: Discussionmentioning
confidence: 98%
“…Other papers suggested that increased VF was a significant predictor of worst disease-free survival in patients with resectable CRC [10] and reduced overall survival in CRC patients receiving adjuvant chemotherapy [16]. In contrast, other works demonstrated that patients with higher VF tended to have better overall-survival that non-visceral obesity patients [12] and a meta-analyses concluded that there was insufficient evidence to prove the presence of a strong link between adiposity and survival [26]. Emerging literature reports the “obesity paradox” in cancer, which suggests that cancer survival is U-shaped and that extremes of weight may have better survival [27, 28].…”
Section: Discussionmentioning
confidence: 99%